STUDI ALTERNATIF PENGENDALIAN BANJIR KOTA TAKALAR - Amir, amir (Universitas Negeri Makassar, 2014)
Environmental conditions in the study site that frequently occurs Takalar City Overflow / floods so that flood patterns control development is necessary to maintain public activities due to infrastructure damage caused by the overflow of Pappa river. This paper aims to establish a model of control by way of the construction of dams, development reservoir regulation, or a combination of regulation and dams. This research uses descriptive quantitative analysis methods and data collection is done through field observations and assisted by a one-dimensional model of program Hec-Ras to analyze the transverse profile streams at once devise alternative flood control overflow of river Pappa. The results showed that the city is in need of a building Takalar flood control due to overflow of river water Pappa. But the most important is community involvement in the maintenance of the existing DAS to keep the water catchment area.